Drug Inventory Management Using The Fuzzy Method In Determining Reorder Points and Maximum Stock in The Pharmacy Installation of Bogor City Hospital - Dessi Maulani Effendy; Ratnawati Prayogi; Alfred Inkiriwang (STABN RADEN WIJAYA WONOGIRI, 2023)
Fuzzy inventory control is an approach to inventory management that uses fuzzy logic to overcome uncertainty and complexity in inventory decision making. In this system, the variables used to control inventory, such as inventory levels, demand levels, and order times, are represented in the form of linguistic variables or Fuzzy sets. The application of Fuzzy inventory control in drug inventory makes it possible to take into account factors such as variations in demand based on seasons, drug priority levels, and patient safety aspects more accurately. The aim of this research is to determine the management of drug supplies in the Chemotherapy, Human Albumin and Antibiotic groups in the Pharmacy Installation at the Bogor City Regional Hospital, to find out the model for planning the need for drugs in the Chemotherapy, Human Albumin and Antibiotic groups using the Fuzzy Inventory Control Method in Bogor City Hospital Pharmacy Installation by looking at the Reorder point and Maximal Stock values, and knowing the comparison of drug planning for the Chemotherapy, Human Albumin and Antibiotic groups with and without the Fuzzy Method Inventory Control at the Bogor City Hospital Pharmacy Installation. The research that will be carried out is quantitative research, which is a type of research that produces discoveries that can be achieved (obtained) using statistical procedures or other methods of quantification (measurement). From the results of the discussion, it can be concluded that the management of the inventory of chemotherapy drugs, human albumin and antibiotics in the pharmacy installation at the Bogor City Regional Hospital is carried out in accordance with the Ministry of Health Regulation Number 72 of 2016, namely the drug planning process, drug request process, process receiving drugs, drug storage processes, and drug distribution processes. Model for planning the need for medicines for the Chemotherapy, Human Albumin and Antibiotic groups using the Fuzzy Inventory Control Method in the Pharmacy Installation of the Bogor City Regional Hospital by looking at the Reorder point and Maximal Stock values. It is known that the Fuzzy design model using input variables for the number of uses and waiting time produces output variables ROP value and maximum stock value. . Comparison of the planning of drugs in the group of Chemotherapy Drugs, Human Albumin and Antibiotics with and without the Fuzzy Inventory Control Method at the Pharmacy Installation of Bogor City Hospital is known to reduce the amount of inventory by 34.49%, streamline the inventory value by 33.97% and increase the ITOR value to 4 times so as to shorten the storage time .